EFFECT OF FOOT MASSAGING ON NAUSEA INTENSITY OF CANCER PATIENTS - T. Najafi Ghezeljeh; F. Rahimiha (Iran University of Medical Sciences, 2004)
Nausea is one of the cancer complaints and its treatments side effect, therefore, proper interventions must be implemented to reduce it. Foot massaging is one of the complementary measures that diminishes nausea intensity. Determining the effect of foot massaging on nausea intensity, we conducted a clinical trial study in which the intensity of nausea was measured and recorded before and after 10 minutes of foot massaging. Contributors were 35 women suffering from cancer, all over 18 years old, which were selected sequentially. Findings showed, statistically significant differences of nausea intensity before and after foot massaging (P<0.0001). To conclude as the result showed lower intensity of nausea after foot massaging, it is the nurse, who can perform it for these kind of patients and also teach the families to provide it for their patients. Similar researches to be conducted in men and also effects of repeated massaging and/or with long or intermediate duration are recommended.